Asessing Hyphotetical Learning Trajectory of Mathematics Teachers - Atikah Sari; Badria Julianti (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
The purpose of this study is to provide an alternative for teachers in preparing teaching materials adapted to track students' mathematics learning in the classroom. This study is a qualitative research with case study method with data collection is a triangulation technique that focuses on 13 people of 5th grade elementary school teacher. The results showed that Hyphotetical Learning Trajectory greatly assist teachers in planning their mathematics teachings, especially in developing teaching materials in a coherent, logical, contextual, and cutting-edge, so that the learning is given to more effectively and efficiently. It was also revealed that the practice of teaching mathematics teacher in the classroom along with lesson plans they have prepared beforehand. Based on the implementation of Hyphotetical Learning Trajectory on mathematics teachers, it can be concluded that the knowledge and skills of teachers in teaching mathematics were well developed; the materials presented are in-depth; it can identify students’ learning; it can anticipate the strategy, representation, and misconceptions of students, so that it can provide an inclusive appropriate the learning needs of their students.